Evidence for geomagnetic excursions recorded in Brunhes and Matuyama Chron lavas from the trans‐Mexican volcanic belt. Issue 6 (14th June 2013) - Michalk, Daniel M.; Böhnel, Harald N.; Nowaczyk, Norbert R.; Aguírre‐Diaz, Gerardo J.; López‐Martínez, Margarita; Ownby, Steven; Negendank, Jörg F. W.
Abstract : [1] This study presents paleomagnetic data from 59 independent lava flows from the trans‐Mexican volcanic belt (TMVB) with ages from 6.4 Ma to recent, 52 being younger than 1 Ma, and 11 new 40 Ar/ 39 Ar age determinations. Most remanence carriers are Ti‐poor titanomagnetite of pseudosingle‐domain magnetic structure, nine lavas contain small amounts of titanomaghemite, and four lavas additional (titano‐) hematite. Paleosecular variation of lava flows younger than 1.7 Ma is consistent with latitude‐dependent Model G and also in agreement with other Pleistocene paleomagnetic data from the TMVB. The directional record of Brunhes and Matuyama Chrons lavas was correlated to the geomagnetic polarity timescale and there is evidence for at least four geomagnetic excursions. One lava flow dated at 592 ± 20 ka has a fully reversed paleodirection and most likely erupted during the Big Lost excursion. Another fully reversed flow, dated at 671 ± 12 ka, gives new volcanic evidence for the Delta/Stage 17 excursion. This excursion is supported by a reversed intermediate direction of another flow from a different volcanic field but of very close age of 673 ± 10 ka. From the Matuyama age lavas, one flow with normal polarity magnetization, dated at 949 ± 37 ka, could either be related to the Kamikatsura or the Santa Rosa excursion and a normal polarity flow, dated at 1628 ± 56 ka, could have been emplaced during the Gilsa excursion. The results presented here confirm in one case but disagree in four cases with results presented in two previous studies of the same lava flows and interpreted as geomagnetic excursions. Key Points: Evidence for at least 4 geomagnetic excursions in 59 Brunhes‐Matuyama lava flows 11 new Ar‐Ar age determinations Results confirm in 1 but disagree in 4 cases with previously published data